Isolation, identification and detection of aflatoxin from date palm (Phoenix dactylifera L.) - M. SENTHIL KUMAR,; D. SURESH, (International Journal of Pharma and Bio Sciences, 2019)
The present study aimed at isolation and identification of fungal community of date palm fruit, as well as detection the Aflatoxin in dates. Observation upon the date fruit sample after incubation revealed that A. flavus, A. niger and Mucor sp were present in the date fruits. Further TLC study showed presence of aflatoxin in the date fruit sample. The UV spectral analysis confirmed the presence of mycotoxins and the results showed the peaks which ranged between 979.2 to 266.3mm. The FT-IR analysis confirmed the presence of mycotoxins showing the FT-IR peaks which ranged between 3463.20 to 429.33cm-1. The HPLC results showed two peaks such as 3.160 and 3.656 were assigned to Citrinin and Ochratoxin compound. A. flavus which is viewed too seriously as may have the potent cell poison. Comsuption of fruits contaminated with fungi may lead to carcinogenic effects in human beings with respectively.